2017
DOI: 10.1016/j.coelec.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Vesicle impact electrochemical cytometry compared to amperometric exocytosis measurements

Abstract: Three new tools are discussed for understanding chemical communication between cells and primarily to delve into the content and structure of nanometer transmitter vesicles. These are amperometric measurements of exocytosis, vesicle impact electrochemical cytometry, and intracellular vesicle impact electrochemical cytometry. These are combining in the end nanoscale mass spectrometry imaging to begin determination of vesicle structure. These methods have provided solid evidence for the concept of open and close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 33 publications
3
35
0
Order By: Relevance
“…Besides, the lower range of the total number of the molecules for doublets and multiplets are similar orders of magnitude to that of the singlets (Table 3B); this suggests the partial release occurrence (Fig. 2E), as proposed in recent studies 54–, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67 during the first peak or the first couple peaks for some of the doublets and multiplets, respectively.…”
supporting
confidence: 83%
“…Besides, the lower range of the total number of the molecules for doublets and multiplets are similar orders of magnitude to that of the singlets (Table 3B); this suggests the partial release occurrence (Fig. 2E), as proposed in recent studies 54–, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67 during the first peak or the first couple peaks for some of the doublets and multiplets, respectively.…”
supporting
confidence: 83%
“…The stimulation-dependent decreases of PC and simultaneous increases of PE and PI levels are likely to facilitate, in some way, the stabilization of the fusion pore during exocytosis. Recently, many studies have suggested that exocytosis, particularly for release from LDCVs, can occur via a mode of partial or “subquantal” release instead of full release, meaning that fused vesicles are able to release only a fraction of the transmitter molecules stored in the vesicle, followed by closure of the fusion pore and a rapid endocytotic process [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. The concept of partial release opens the probability for the cell to adjust the vesicular transmitter load, in addition to exocytotic release, and offers a versatile pathway for a biological system to respond to the rapid change of the surrounding environment.…”
Section: Discussionmentioning
confidence: 99%
“…Since electron transfer do not readily occur across a bilayer lipid membrane, the electrolysis of the liposome redox active content after collision and membrane rupture or opening at the electrode surface provides insights on the membrane permeation mechanism. [12][13][14]16,17 According to Ewing and co-workers, the so-called vesicle impact electrochemical amperometry is mainly driven by an electroporation process of the vesicle membrane on polarized carbon UMEs which leads to the vesicle rupture and the electrolysis of its content. [18][19][20][21] Vesicle membrane opening by electroporation is strongly dependent on lipid membrane properties, liposome content, vesicle size, temperature, electrode potential, the nature of the electrode and probably the concentration of redox species inside and outside the liposome.…”
Section: /19mentioning
confidence: 99%